Comparison of toxins of Clostridium butyricum and Clostridium botulinum type E. - Giménez, J A (1988)
The toxin of Clostridium butyricum strains isolated from two infants with botulism is neutralized by antitoxin for type E botulinum toxin. This toxin and that of a C. botulinum type E strain were purified by the same protocol. Both toxins were Mr 145,000 proteins which, when activated with trypsin, were composed of an H subunit of Mr 105,000 and an L subunit of Mr 50,000. The activated specific toxicity of purified butyricum toxin based on an intravenous assay was 2 X 10(8) mouse 50% lethal doses (LD50s)/mg of protein, but that based on an intraperitoneal assay was 7 X 10(7) LD50s/mg, compared with 6 X 10(7) LD50s/mg for type E toxin as determined by both methods. Immunodiffusion tests with antitoxin raised with type E toxin indicated that the two toxins were serologically very similar except for a spur formed by type E toxin. The close similarities of the two toxins suggest that toxigenic C. butyricum could arise when a wild-type strain, which is normally nontoxigenic, acquires the toxin gene of a C. botulinum type E strain.